HUBUNGAN PERILAKU PETANI DENGAN ADOPSI TEKNOLOGI PASCA PANEN KOPI ROBUSTA DI KABUPATEN TEMANGGUNG - Titis Aditya Santoso; Tutik Dalmiyatun; Kadhung Prayoga (Universitas Tidar, 2021)
The traditional post-harvest handling of robusta coffee doesn’t provide good quality results, which then motivates the government to take steps by providing technological assistance in stages. The research was aimed to determine the adoption process of robusta coffee post-harvest technology and analyze the correlation between attitudes, risk-taking courage, and skills on the adoption of coffee farmers' technology in Temanggung Regency. The location of this research was determined purposively. The number of respondents was 94 samples using Slovin method and taken from three villages, consist of Giyono, Jamusan, and Jombor. The post-harvest technology used by farmers in Jumo District were wet processing, dry processing, roasting, and coffee bean packaging technology. The results showed that farmers in Jumo District have gone through five stages of adoption in adopting the post-harvest technology assistance provided, namely awareness, interest, evaluation, trial, and adoption. Significantly, there is a very close relationship between attitudes, courage to take risks and skills towards technology adoption with correlation coefficient values were 0.896, 0.929, and 0.900, respectively. There needs to be more intensive assistance to improve farmer skills in using post-harvest robusta coffee technology, especially for farmers in the older age group and farmers with low education.Keywords: behavior, post-harvest, robusta coffee, technology adoption.